Development of the technology for changing the sequence of access to shared resources of business processes for process management support - Chalyi, Serhii; Levykin, Ihor; Biziuk, Andrii; Vovk, Aleksandr; Bogatov, Ievgen (Eastern-European Journal of Enterprise Technologies, 2020)
The model of the event log of the information system has been improved. The model contains the sequences of events consistent with implemented sequences of management actions within both the process approach and functional management approach. A strict linear order in time was assigned for each pair of events belonging to the same process. The model is designed to describe the prototype of the as-is business process. A case-based model of a business process, describing the features of its known implementations, reflected in the event log, has been proposed. The model combines a set of implemented sequences of operations of each process and takes into consideration the time to implement these operations, as well as the resources they need. When describing the time to implement the operations of a process, delays in accessing the company’s shared resources are taken into consideration. The model makes it possible to predict the terms of completing the set of business processes competing for the resources when removing or adding new processes to this set. The technology for changing the sequence of access to resources for a set of business processes competing for these resources within the process management was developed. The proposed technology uses the case-based model of a business process to calculate the order of access to resources. The technology provides an opportunity to calculate the total reduction in delays over the implementation time in relation to the implementation terms when processes are competing for resources. The technology makes it possible to choose how to access resources with the least delay in relation to operations completion deadlines for the known variants of a business process implementation. This enables a DM to assess the possibility of launching new processes that use shared resources by reducing the waiting time when accessing these resources